The Parker inheritance - Johnson, Varian 1977- (Arthur A. Levine Books, an imprint of Scholastic Inc., 2018)
Twelve-year-old Candice Miller is spending the summer in Lambert, South Carolina, in the old house that belonged to her grandmother, who died after being dismissed as city manager for having the city tennis courts dug up looking for buried treasure...but when she finds the letter that sent her grandmother on the treasure hunt, she finds herself caught up in the mystery and, with the help of her new friend and fellow book-worm, Brandon, she sets out to find the inheritance, exonerate her grandmother, and expose an injustice once committed against an African American family in Lambert